Android phone remote control for Canon camera II - Raphael Ardyanto Sunardi (2012)
DSLR camera has become main part of the photography world nowadays. With the technology underneath DSLR camera, the configuration of the camera can be adjusted electronically to produce images according to what the photographer wants. However, sometimes the photographer needs to get an image at a certain angle in which is not possible to take because the photographer cannot see the object to be taken from the camera. That obstacle faced by photographer inspires this project to create software which enables user to have a more portable access to the camera. This software enables user to control of the camera and preview the image before the image is captured using a mobile device. The software created in this project was developed under Android environment. The reason is as follow. First, Android has been used for most of the mobile devices in the world, from tablets into mobile phone. Second, the Android provides an open source software development kit which enables developers to develop various applications for many Android devices. Third, the language that is supported by Android SDK is Java, which has been used in many course experiments in Computer Engineering, enabling us to develop the application in this project in a friendlier environment.